Yuan-Hu Zhi Tong Prescription Mitigates Tau Pathology and Alleviates Memory Deficiency in the Preclinical Models of Alzheimer’s Disease - Iyaswamy, A.; Krishnamoorthi, S. K.; Liu, Y. W.; Song, J. X.; Kammala, A. K.; Sreenivasmurthy, S. G.; Malampati, S.; Tong, B. C. K.; Selvarasu, K.; Cheung, K. H.; Lu, J. H.; Tan, J. Q.; et al. (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is characterized by memory dysfunction, Aβ plaques together with phosphorylated tau-associated neurofibrillary tangles. Unfortunately, the present existing drugs for AD only offer mild symptomatic cure and have more side effects. As such, developments of effective, nontoxic drugs are immediately required for AD therapy. Present study demonstrates a novel role of Chinese medicine prescription Yuan-Hu Zhi Tong (YZT) in treating AD, and it has substantiated the in vivo effectiveness of YZT in two different transgenic mice models of AD, namely P301S tau and 3XTg-AD mice. Oral treatment of YZT significantly ameliorates motor dysfunction as well as promotes the clearance of aggregated tau in P301S tau mice. YZT improves the cognitive function and reduces the insoluble tau aggregates in 3XTg-AD mice model. Furthermore, YZT decreases the insoluble AT8 positive neuron load in both P301S tau and 3XTg-AD mice. Using microarray and the “Connectivity Map” analysis, we determined the YZT-induced changes in expression of signaling molecules and revealed the potential mechanism of action of YZT. YZT might regulate ubiquitin proteasomal system for the degradation of tau aggregates. The research results show that YZT is a potential drug candidate for the therapy of tau pathogenesis and memory decline in AD.